Fostering foreign direct investment in the `new' South Africa in the context of a changing world trading system: challenges, opportunities, policies - Moloi, Sehloho Francis (Department of Commercial Law, 2021)
The focus of this thesis is on foreign direct investment (FDI). This is an aspect of international trade that has recently become increasingly important, not only to developing and developed countries in general, but to South Africa in particular; notably so when this country was admitted back to the larger international community of nations after April 1994. In the quest to address the many imbalances engendered by apartheid, South Africa's . ' policy-makers maintain that FDI may play a critical role in helping achieve the goals and objectives of the government's Reconstruction and Development Programme (RDP). It is for this reason that the creation of a climate conducive to both local and foreign investment is expected to be one of the top priorities of the new government of national unity (GNU). The important point stressed in this thesis is that, when devising policies and strategies aimed at increasing trade flows and attracting foreign investment into the 'new' South Africa, this country's policy-makers should, always, take into account the profound changes that the world trading system is currently undergoing. The current trends in world trade, FDI and regional integration are poised to influence the position of South Africa and the role it may play in the world economy of the 1990s and beyond. The writer of this thesis believes that the daunting challenge facing South Africa's policymakers is to understand these patterns and changes, as well as forces behind them, as a basis for developing the ability to respond constructively and positively. This is important, because this country will be expected to play its respective role according to the existing rules of the prevailing world economic order. In short, South Africa's policy-makers are faced with the task of devising some ingenious strategies and policies that may maximise the opportunities provided for South Africa by the new world trading environment. At the same time, those measures should also aim to minimise the potential negative effects arising from increased world-wide competition for international markets, trade and investment funds. The point is also made however, that the effectiveness of such strategies and policies will depend in large part on South Africa's efforts and political will to adjust to the new opportunities and challenges of the international trading environment. This thesis comprises four chapters. Chapter One discusses trends in world trade, FDI and regional integration in the 1990s and their possible implications for South Africa. Its aim is to provide the reader with a fuller appreciation of the international context within which South Africa's future trade and investment policies should be considered and implemented; because whatever approach South Africa adopts, it is imperative that it must be viable in the world trading environment of the 1990s. It will be shown for instance that, although the world trading environment of the 1990s is characterised by rapid 'globalisation' of world markets and proliferation of inward-looking regional trading arrangements (RT As), this decade is experiencing, on the one hand, growing 'protectionism' and concentration of world trade and investment funds in the developed market economies and greater marginalisation of the developing and least developed (LDCs) countries on the other. It will be shown further that these phenomena have a negative impact on the ability of the latter countries to play a meaningful role in international trade and investment. Chapter One concludes by looking at the World Trade Organisation (WTO) and the impact it will have on international trade relations in the 1990s and beyond. Chapter Two discusses the various determinants of FDI. In this chapter, it will be demonstrated that many analysts and governments hold the view that FDI is a 'good thing' as it is perceived to have a positive impact on other economic variables such as balance-of-payments, employment and capital creation, access to new markets and technological know-how. It will also be shown that in fact, many developing and transition countries are engaged in fierce competition for foreign investment, and that to this end, these countries have recently changed their respective foreign investment laws with the sole aim of creating a climate attractive to foreign investment in their respective economies. The determinants of FDI in this chapter are discussed under the following headings, viz. government policies ( e.g. ownership policies, taxation and subsidies, convertibility of foreign exchange and remittance of earnings, performance requirements, capital and price controls, etc.), locational determinants (e.g. host comparative advantage, host market size, etc.), structural determinants (e.g. economic 'openness', investment infrastructure, etc.), and economic determinants (e.g. international trade links, etc.). The impact of these various determinants will also be discussed as well as policy implications for South Africa. Chapter Three discusses the current constraints and opportunities for the 'new' South Africa in the quest for increased foreign-direct-investment-flows. It will be argue.d that although South Africa has deep-seated structural problems ( e.g. shortage of foreign capital and skills, lack of international competitiveness of its manufactured products, chronic unemployment, etc.), this country stands a good chance (given its developed infrastructure and a relatively dynamic manufacturing sector by African standards for instance) of being a possible destination for FDI and international trade flows. The last Chapter (Four) discusses various policy implications for South Africa in its attempt to attract FDI into this country. It will be demonstrated that whatever approach South Africa adopts, will be impacted upon by various factors, inter alia, the prevailing world trading environment, growing protectionism in the developed market economies, its obligations under the WTO, its trade relations with other SACU and SADC countries, and so on. It is suggested that South Africa's current trade regime needs to be overhauled as it is not conducive to the development of competitive industrial capabilities inter alia, due to a strong anti-export bias that is inherent in its policies. It will also be argued that the state - like in other high-growth East Asian economies - has an important role to play in fostering the competitiveness of certain industries for instance, as a way of promoting the international competitiveness of South Africa's manufactured products. The Conclusion summarises briefly the major issues covered in this thesis. Before turning to Chapter One it is important to make the following point: the idea of FDI is broad, controversial and multi-faceted. The writer of this thesis does not claim to provide a definitive account of how South Africa should deal with this complex phenomenon. On the contrary, this thesis should be treated merely as an attempt to provide a broad introductory overview from the South African perspective, of how this country could begin to address the issue of FDI with the aim of addressing its economic and trade problems, in the context of a changing world trading system of the 1990s.